2022
DOI: 10.3390/cancers14020363
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-1 Influences Prostate Cancer Cell Growth and Invasion through an Integrin α3, α5, αV, and β1 Dependent Mechanism

Abstract: Insulin-like growth factor-1 (IGF-1)-related signaling is associated with prostate cancer progression. Links were explored between IGF-1 and expression of integrin adhesion receptors to evaluate relevance for growth and migration. Androgen-resistant PC3 and DU145 and androgen-sensitive LNCaP and VCaP prostate cancer cells were stimulated with IGF-1 and tumor growth (all cell lines), adhesion and chemotaxis (PC3, DU145) were determined. Evaluation of Akt/mTOR-related proteins, focal adhesion kinase (FAK) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…In PCa cells treated by metformin, c‐Myc protein levels are reduced and AR signaling could be suppressed 27 . Additionally, metformin could inhibit androgen‐dependent upregulation of insulin‐like growth factor receptor type I 28 responsible for promoting the survival, development, and proliferation of PCa cells 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PCa cells treated by metformin, c‐Myc protein levels are reduced and AR signaling could be suppressed 27 . Additionally, metformin could inhibit androgen‐dependent upregulation of insulin‐like growth factor receptor type I 28 responsible for promoting the survival, development, and proliferation of PCa cells 29 …”
Section: Discussionmentioning
confidence: 99%
“… 27 Additionally, metformin could inhibit androgen‐dependent upregulation of insulin‐like growth factor receptor type I 28 responsible for promoting the survival, development, and proliferation of PCa cells. 29 …”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with a growing body of literature that suggests that increases in circulating levels of insulin or insulin-like molecules may be more directly promoting the progression of multiple cancer types more so than other conditions associated with obesity/high body mass index (BMI) [ 41 , 42 ]. To that end, prior studies have demonstrated that insulin and IGF-1 can directly stimulate the proliferation of a subset of cancer cells including TRAMP-C3 prostate cancer cells [ 43 , 44 ]. Arguing against a specific role for IGF-1 is a prior report that liver-specific deletion of Igf1 in TRAMP mice did not impact tumor progression [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 DEGs were associated with focal adhesion signaling pathway, including one upregulated gene ( THBS4 ) and 21 downregulated genes ( PRKCA , ITGB8 , MYLK , FLNA , VCL , CCND2 , MYL9 , THBS1 , ITGA5 , COL6A3 , LAMB1 , TNC , CAV1 , FLNC , PRKCB , COL6A2 , IGF1 , PGF , COL6A1 , ITGA8 , PDGFC ). Of these, the key gene IGF1 has been reported to drive the fine-tuning network between the integrin-FAK signaling and the Akt-mTOR pathway, thus promoting the growth and invasion of PCa cells ( Siech et al, 2022 ). Furthermore, Shorning et al (2020) found that PI3k-Akt signaling pathway could interact with other oncogenic signaling cascades, like androgen receptor, thereby stimulating the growth and developing drug resistance of PCa cells ( Shorning et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%